2020
DOI: 10.1038/s41598-020-59595-y
|View full text |Cite
|
Sign up to set email alerts
|

Resource use by individual Drosophila suzukii reveals a flexible preference for oviposition into healthy fruits

Abstract: The invasive pest fruit fly Drosophila suzukii is thought to be a specialist on healthy, i.e. unwounded, non-fermenting fruits. Morphological (sharp ovipositor) and neurophysiological/behavioural adaptations have been suggested to contribute to distinct adult feeding (wounded/microbe-laden fruits) and reproductive (healthy fruits) sites. We tested whether (1) variation in the overall availability of fruits, (2) variation in fruit type (healthy, wounded, fermenting), and (3) the relative abundance of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
(15 reference statements)
3
32
0
Order By: Relevance
“…Karageorgi et al . [ 6 ] showed that when given the choice between ripe and rotten strawberry fruits, D. suzukii strongly preferred ripe over rotten fruit, whereas Drosophila melanogaster showed an opposite tendency and preferred rotten fruit, consistent with other studies [ 7 , 8 ]. In the same experiment, Drosophila biarmipes , a closely related species of D. suzukii showed no preference between ripe and rotten fruit, indicating that they are at an intermediate evolutionary stage between D. suzukii and D. melanogaster .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Karageorgi et al . [ 6 ] showed that when given the choice between ripe and rotten strawberry fruits, D. suzukii strongly preferred ripe over rotten fruit, whereas Drosophila melanogaster showed an opposite tendency and preferred rotten fruit, consistent with other studies [ 7 , 8 ]. In the same experiment, Drosophila biarmipes , a closely related species of D. suzukii showed no preference between ripe and rotten fruit, indicating that they are at an intermediate evolutionary stage between D. suzukii and D. melanogaster .…”
Section: Introductionsupporting
confidence: 82%
“…Assessing the fruit condition and making the decision to select the oviposition site involve an integration of multiple sensory cues. It has been shown that D. suzukii has the ability to make complex decisions between healthy and fermenting fruits depending on the availability of the resource [ 8 ]. We hypothesize that one of the unexplored factors that D. suzukii sense could be the commensal microbes on fermenting fruits that have been deposited by conspecific and heterospecific individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In late fruiting season when the majority of the fruits are on the ground and rotten, the females may readily lay eggs onto suboptimal fermenting fruits, the situation resembling our assays using only inoculated substrates (figure 3). These explanations are consistent with the study by Kienzle et al [8], which showed that D. suzukii exhibit stronger preferences toward ovipositing in healthy fruits when healthy and fermenting fruits are both abundant compared to when the former are less abundant. The context dependent optimization through seasonal change in host fruit condition might explain the evolutionary background of our findings where substrate hardness takes precedence over microbial presence in the decision to oviposit in this species.…”
Section: Discussionsupporting
confidence: 93%
“…Karageorgi et al . [6] showed that when given the choice between ripe and rotten strawberry fruits, D. suzukii strongly preferred ripe over rotten fruit, whereas D. melanogaster showed an opposite tendency and preferred rotten fruit, consistent with other studies [7,8]. In the same experiment, D. biarmipes , a closely related species of D. suzukii , showed no preference between ripe and rotten fruit, indicating that they are at an intermediate evolutionary stage between D. suzukii and D. melanogaster .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation